A Case of GM 1 Gangliosidosis Type 2 Mimicking Zellweger Syndrome (Global Journal of Medical Research, 2023)
Juvenile GM1-gangliosidosis also known as type II or juvenile GM1-gangliosidosis is an autosomal recessive lysosomal storage disorder that clinically differs from infantile GM1- gangliosidosis in the absence of the characteristic cherry-red patch and hepatosplenomegaly The disease is characterized by mild skeletal abnormalities and slowly progressing neurodegeneration Due to the late age of onset and unusual presentation diagnostic confusion with other ataxic and purely neurological disorders is common There are currently 3 4 recognized types of GM1-gangliosidosis with type I being the most prevalent phenotype with an average onset age of 6 months Several subtypes of GM1-gangliosidosis are caused by mutations in the GLB1 gene but the location and type of deleterious mutations have a direct impact on the severity of the disease and the age at which it manifests
Keywords: GM1 gangliosidosis; lysosomal storage disease; beta-galactosidase